Welsh Speakers’ Dementia Care - Alzheimer's Society Cymru; Welsh Language Commissioner (Welsh Government, 2018)
The Welsh Language Commissioner and Alzheimer’s Society Cymru have collaborated on a project focussing on the Welsh language and dementia. The research company Wavehill was commissioned to undertake a study of the care and support services delivered to Welsh speakers with dementia. This qualitative research involved consultation with senior officers from local authorities and health boards; academics in the field; care and support providers; and people living with dementia. The purpose of the study was to investigate the main factors and themes influencing the provision, or lack of provision, of Welsh medium dementia health and support services, and learn about the experience of Welsh speakers with dementia of that provision. A round-table event was held with experts in the field to discuss the findings of the research and offer possible policy solutions in response to the difficulties identified. This document summarises the findings of the project. Firstly, it outlines the nature of dementia and highlights the relevant language considerations. It then discusses the policy and legislative developments that are relevant to the field. We then present the findings of our research and the experiences of those living with dementia of the Welsh medium care available to them. Finally, it highlights the difficulties identified and the policy solutions which could, if adopted, make a positive difference to the provision for Welsh speakers.

Does end-of-life care differ for Anglophones and Francophones? A retrospective cohort study of decedents in Ontario, Canada - Guerin, Ewa; Batista, Ricardo; Hsu, Amy. T.; Gratton, Valérie; Chalifoux, Mathieu; Prud’homme, Denis; Tanuseputro, Peter (Journal of Palliative Medicine, 2018)
Background: Approximately half of decedents in Ontario, Canada, receive some palliative care, but little is known about the influence of language on the nature of these services. Objective: To examine differences between English- and French-speaking residents of Ontario in end-of-life care and outcomes (e.g., health care costs and location of death). Design: A retrospective cohort study using multiple linked databases. Setting/Subjects: A population-based cohort of decedents in Ontario (2010–2013) who were living in long-term care institutions (i.e., nursing homes) or receiving home care before death (N = 25,759). Data from two regions with higher representations of Francophones were examined, with the final distribution by primary language being 75% Anglophone, 18% Francophone, and 7% other languages. Results: Compared with Anglophones, Francophones were more frequent users of long-term care (47.6% vs. 37.1%) and less frequent users of home care (71.3% vs. 76.3%). In adjusted models, the number of days spent in hospital in the last 90 days of life was similar between Anglophones and Francophones, although the odds of dying in hospital were significantly higher among the latter. The mean total health care cost in the last year of life was slightly lower among French ($62,085) compared with English ($63,814) speakers. Conclusions: There are statistically significant differences in end-of-life outcomes between linguistic groups in Ontario, namely more institutionalization in long-term care, less home care use and more deaths in-hospital among Francophones (adjusted). Future research is needed to examine the cause of these differences. Strategies to ensure equitable access to quality end-of-life care are required.

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Étude de la situation socioculturelle et linguistique des jeunes franco-ontariennes et franco-ontariens face aux défis d’accès aux services de santé de qualité en français à Timmins - Mafanda-Mahuma, Pierre (Université Laurentienne, 2018)

La recherche en santé et en services sociaux auprès des populations francophones en situation minoritaire au Canada. Revue de littérature et analyse des thèmes de recherche (2014-2016) - Sauvageau, Marie-Michèle (Association des collèges et universités de la francophonie canadienne, 2018)